Self-Efficacy, Work-Family Conflict, Social Support, Gender Role Attitude and Role Model as Antecedents of Career Aspiration among Women in Middle Management - Wu, Hwei Ming (2007)
Overall, most of the studies on career aspiration were focused on college students and very rarely on working adults. There were yet very few empirical investigations that studied about factors that contributed to aspiration of advancing to upper level position especially the aspiration to top management among working women in middle management. The purposes of this study were to find out the relationship of self-efficacy, work family conflict, social support, gender role attitude, role model and career aspiration to top management among women in middle management at the manufacturing line. Besides, this study intended to determine the contribution of each factor to career aspiration. Using questionnaires, data were obtained from 109 married women in middle management at eight private manufacturing companies located in Bangi and Nilai. The staff in middle management included executives, senior executives and assistant managers. Descriptive statistical analysis, Pearson Product-Moment correlation and regression analysis were employed to analyze the data. This study found that self-efficacy, social support, gender role attitude and role model were significantly related to career aspiration (p<0.05). Specifically, self-efficacy and gender role attitude were the most significant antecedents of career aspiration among women in middle management at the manufacturing line. Overall there was 41.4% of the variability in career aspiration was explained by self-efficacy, work family conflict, social support, gender role attitude and role model influence. Strengthening support system and confidence stimulation program could be the most effective way to improve the career aspiration among working women in the middle management. Given the importance of self-efficacy, it is crucial for career counselors to develop interventions that build up the middle management women’s confidence and increase their self-efficacy. Further studies are expected to compare the antecedents of career aspiration among different age, religious or ethnic groups of middle management women. Nevertheless, future studies should be carried out for other service sectors such as banking, education and insurance in which female staff are the major composite.